2010
DOI: 10.1007/s00018-010-0435-2
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial dynamics in cell death and neurodegeneration

Abstract: Mitochondria are highly dynamic organelles that continuously undergo two opposite processes, fission and fusion. Mitochondrial dynamics influence not only mitochondrial morphology, but also mitochondrial biogenesis, mitochondrial distribution within the cell, cell bioenergetics, and cell injury or death. Drp1 mediates mitochondrial fission, whereas Mfn1/2 and Opa1 control mitochondrial fusion. Neurons require large amounts of energy to carry out their highly specialized functions. Thus, mitochondrial dysfuncti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
206
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 265 publications
(208 citation statements)
references
References 162 publications
1
206
0
1
Order By: Relevance
“…Disruption of mitochondrial morphological dynamics sensitizes cells to apoptotic cell death (9,24,25), and recent studies have reported that disturbances within the balance of these two processes can implicate the outcome of cardiovascular disease and neurodegenerative disease (20). In this study, we show that ischemic challenge in myocytes promotes translocation of Drp1 to His-Pim-1 (wild-type, kinase dead) was expressed in Escherichia coli and affinitypurified for use in the kinase assay.…”
Section: Discussionmentioning
confidence: 77%
See 1 more Smart Citation
“…Disruption of mitochondrial morphological dynamics sensitizes cells to apoptotic cell death (9,24,25), and recent studies have reported that disturbances within the balance of these two processes can implicate the outcome of cardiovascular disease and neurodegenerative disease (20). In this study, we show that ischemic challenge in myocytes promotes translocation of Drp1 to His-Pim-1 (wild-type, kinase dead) was expressed in Escherichia coli and affinitypurified for use in the kinase assay.…”
Section: Discussionmentioning
confidence: 77%
“…S1 D and E). Previous studies have shown that phosphorylation of Drp1-S637 reduces mitochondrial fragmentation, Drp1 accumulation at the mitochondria, and apoptotic cell death (19,20). Because we have established that Pim-1 kinase preserves mitochondrial integrity and function (15), we investigated whether Pim-1 expression could affect pDrp1-S637 levels.…”
Section: Drp1mentioning
confidence: 99%
“…Although cocaine-or alcohol-induced histone H3K4me3 changes were not directly predictive of gene expression at the individual gene promoter level, the observed histone H3K4me3 profiles still provide valuable insight into the addiction-induced alteration of histone structure. Mitochondrial inner membrane dysfunctions are known to play critical roles in neurodegenerative diseases such as Huntington disease, Alzheimer disease, and Parkinson disease (21). The main dysfunctions involved in the pathological processes are suppressed oxidative stress defense, altered membrane ion permeability, and, particularly, depleted ATP synthesis resulting from the inhibition of components of the oxidative phosphorylation pathway.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the importance of mitochondrial dynamics has been documented in neuronal development (Li et al, 2004;Dickey and Strack, 2011;Chan, 2006;Ishihara et al, 2009) and survival Merrill et al, 2013;Dagda et al, 2008;Merrill et al, 2011;Cho et al, 2010;Nakamura et al, 2010). However, also there, the specific mechanisms often await elucidation.…”
Section: Introductionmentioning
confidence: 99%